Motor system modulation by transcranial alternating current stimulation: insights from functional MRI—a scoping review - Han, Simon; Luo, Jason; Vo, Ivy Tuong Van; Chang, Won Kee; Paik, Nam-Jong; Choi, Ji Soo; Kim, Won-Seok (Frontiers in Neurology, 2025)
Transcranial alternating current stimulation (tACS) is a non-invasive neuromodulation technique that delivers oscillatory currents to modulate endogenous brain rhythms. Frequency-specific effects on motor function have been reported, yet the neural mechanisms remain incompletely understood. This scoping review synthesizes functional MRI (fMRI) evidence on tACS-induced modulation of motor-related brain activity and connectivity in healthy individuals and patients with neurological conditions. A systematic search of the literature identified six eligible studies with a total of 108 participants, of whom 26 were individuals with chronic stroke. Stimulation frequencies ranged from 5 to 70 Hz, most often targeting the primary motor cortex. Gamma-band tACS (≥50 Hz) was generally associated with increased task-related activation and strengthened connectivity within sensorimotor networks in healthy participants, whereas alpha- and beta-band stimulation produced variable or region-specific effects. In the chronic stroke group, 10 Hz tACS enhanced localized activation, while 20 Hz tACS promoted broader network integration. These findings suggest that tACS may modulate motor networks in a frequency- and site-dependent manner, with preliminary implications for post-stroke rehabilitation. However, substantial heterogeneity in study design, stimulation parameters, and analysis approaches limits direct comparison across studies. Standardized protocols, larger clinical trials, and multimodal approaches integrating fMRI with electroencephalography are warranted to clarify underlying mechanisms and optimize tACS applications for motor recovery.